‘GLOBAL NORTH AND GLOBAL SOUTH’: THE SIGNIFICANCE AND MEANING OF THESE TERMS FOR OUR UNDERSTANDING AND PRACTICE OF MISSION - NGURSANGZELI BEHERA, Marina (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2019)
The paper explores the metaphors of Global South and North. Looking at earlier terms such as the first, second and third world and identifying the changes coming with the shift of gravity in the World of Christianity and those after the year 1989 as important moments to start speaking of global Christianity, Global North and South, it is not the geography of places but the interrelations – economic, political, cultural, religious - of the various contexts which determine a meaningful usage of these terms. The interrelations are used as a background to discuss the paradigm of mission from the margins from the perspective of the author who hails from Northeast India - considered to be part of the global South – and working in a center for mission studies in the Global North.